Efektifitas Pemanfaatan Komik Kesehatan dalam Upaya Mengenal Tanda, Gejala dan Pencegahan Keputihan Patologis - Intan Kumalasari; Indah Dewi Ridawati; Herawati Jaya (STIKes Hang Tuah Pekanbaru, 2022)
Vaginal discharge is the most common health problem faced by adolescents and requires special attention. The limited availability of direct and effective health education media, such as comics, is one of the factors behind the low awareness of adolescents in caring for their reproductive organs. Comic media is widely accepted as a teaching tool among students, but the availability of comics that focus on health issues is still very limited. This study aims to determine the effectiveness of the use of health comics in an effort to recognize the signs, symptoms and prevention of pathological vaginal discharge. This study was conducted at SMAN 1 Musirawas in August 2021. The study design was Quasi Experimental, used one group with pretest-posttest. The sample was 66 respondents who were selected by purposive sampling technique. Data were collected in two stages, before and after the educational intervention using two instruments, namely the characteristics of the respondents and knowledge about pathological vaginal discharge. The reliability test of the questionnaire used the split half technique with a 71% variable level. The data were analyzed using the Wilxocon test. The results of the analysis showed that there was an increase in knowledge in an effort to recognize the signs, symptoms and prevention of pathological vaginal discharge after being given an intervention with Health Comics on the posttest results with an increase of 24,28% and an increase in the average score of 7,2 points. It was concluded that educational intervention with Health Comics was effective in increasing students' knowledge in an effort to recognize the signs, symptoms and prevention of pathological vaginal discharge in students of SMAN I Musirawas.